2020
DOI: 10.1093/infdis/jiaa350
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-β-1a Inhibition of Severe Acute Respiratory Syndrome–Coronavirus 2 In Vitro When Administered After Virus Infection

Abstract: The ongoing coronavirus disease 2019 pandemic has forced the clinical and scientific community to try drug repurposing of existing antiviral agents as a quick option against severe acute respiratory syndrome–coronavirus 2 (SARS-CoV-2). Under this scenario, interferon (IFN) β-1a, whose antiviral potential is already known, and which is a drug currently used in the clinical management of multiple sclerosis, may represent as a potential candidate. In this report, we demonstrate that IFN-β-1a was highly effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 15 publications
4
71
0
1
Order By: Relevance
“…Importantly, IFN responses were found to be milder than TNF-NFkB signaling in our model. SARS-CoV-2 has been shown to be sensitive to IFNλ and IFNβ treatment, so the absence of a robust IFN response in AT2s, if verified in vivo, would have significant clinical implications and might suggest pathways to augment therapeutically in COVID-19 patients before they progress to ARDS [20][21][22] . In prior studies of cell lines that lacked AT2-specific gene expression, the absence of a robust IFN response was overcome by using a high MOI for infection 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, IFN responses were found to be milder than TNF-NFkB signaling in our model. SARS-CoV-2 has been shown to be sensitive to IFNλ and IFNβ treatment, so the absence of a robust IFN response in AT2s, if verified in vivo, would have significant clinical implications and might suggest pathways to augment therapeutically in COVID-19 patients before they progress to ARDS [20][21][22] . In prior studies of cell lines that lacked AT2-specific gene expression, the absence of a robust IFN response was overcome by using a high MOI for infection 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the protective effect of type I IFN associated with antiviral therapies for patients with SARS and MERS [reviewed by Sallard et al (334)], which arouses the interest of the scientific community in type I IFN as a potential treatment against SARS-CoV-2 (334)(335)(336)(337). Despite their efficacy against SARS-CoV-2 (338,339), the results of in vitro studies using IFN-a and -b to treat COVID-19 patients remain inconclusive.…”
Section: Antiviralsmentioning
confidence: 99%
“…A recent study of SARS-CoV-2 infection has reported that type III and type-I interferons are downregulated both in SARS-CoV-2 infected cells and in the lung tissue of patients deceased with COVID-19 (7), suggesting a pathogenic mechanism similar to that hypothesized for SARS-CoV and MERS-CoV (8). Furthermore, some from our group have recently shown that IFNβ inhibits replication of SARS-CoV-2 in vitro (9).…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 80%
“…[Time frame: baseline, days3,5,7,9,11,13,15, 21, 29]. IFNβ-1a has direct in vitro antiviral activity against SARS-CoV-2(9), while IFNβ-1b has been identi ed as the key therapeutic reducing the time to negative conversion of SARS-CoV-2 nasopharyngeal swabs in a recent trial(11).Secondary outcomes I)a. Improvement in clinical severity score, de ned as percentage of patients reporting each severity rating on a 7-point ordinal scale (as de ned above in the Eligibility criteria {10}).…”
mentioning
confidence: 99%